Risk factors for postoperative DVT exacerbation or new DVT in patients with spinal cord injury complicated with cervical fracture - Wang, Haiying; Lv, Bing; Li, Wei; Xu, Jingjing; Ma, Ce (Frontiers in Cardiovascular Medicine, 2024)
Objective To investigate the dynamic changes of perioperative deep venous thrombosis (DVT) in patients with spinal cord injury complicated with cervical fracture and analyze the risk factors of postoperative DVT exacerbation or new DVT. Methods From January 2018 to December 2023, a total of 232 patients with spinal cord injury complicated with cervical fracture in our hospital were retrospectively analyzed. Ultrasonography of both lower limbs was performed before and after surgery. According to whether there was aggravation of DVT or new thrombosis, the group was divided into DVT exacerbation or new DVT group and non-DVT exacerbation group. Clinical data were used to study the dynamic changes of perioperative DVT. Logistic regression analysis and receiver operating characteristic (ROC) curve were used to explore the risk factors. Results The DVT was found in 47 patients before surgery, including 26 cases of distal thrombus, 14 cases of mixed thrombus and 7 cases of proximal thrombus. Postoperative DVT increased to 81, including 31 distal thrombus, 35 mixed thrombus and 15 proximal thrombus. A total of 53 patients (22.8%, 53/232) experienced postoperative DVT exacerbation or new DVT. Logistic regression analysis revealed that age, American Spinal Injury Association (ASIA) score, time from injury to surgery, surgery time and blood loss were risk factors for postoperative DVT exacerbation. Conclusions In patients with spinal cord injury complicated with cervical fracture, the risk of postoperative DVT exacerbation is very high. Age, ASIA score A-B, time from injury to surgery, surgery time and blood loss were risk factors for postoperative DVT exacerbation or new DVT.